2010
DOI: 10.1073/pnas.1003115107
|View full text |Cite
|
Sign up to set email alerts
|

Engineered RNA viral synthesis of microRNAs

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs that exert posttranscriptional gene silencing and regulate gene expression. In addition to the hundreds of conserved cellular miRNAs that have been identified, miRNAs of viral origin have been isolated and found to modulate both the viral life cycle and the cellular transcriptome. Thus far, detection of virus-derived miRNAs has been largely limited to DNA viruses, suggesting that RNA viruses may be unable to exploit this aspect of transcriptional regulation. Lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 39 publications
4
98
0
Order By: Relevance
“…As a similar inability to generate K219R mutants was previously reported by others (30), we considered that this issue likely indicated that the N62H mutation in NS2 was lethal. Therefore, to allow us to test the relevance of NS1 SUMOylation in the absence of changes in the primary sequence of NS2, we followed a previously reported methodology to separate the ORF for NS1 from that for NS2 while still allowing NS2 to be produced as a splicing product of the primary NS mRNA transcript (57). Briefly, starting with PolI-driven constructs for either wt NS1 or NS1K70AK219A, the splicing acceptor site located in NS1 was inactivated by site-directed mutagenesis.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 99%
“…As a similar inability to generate K219R mutants was previously reported by others (30), we considered that this issue likely indicated that the N62H mutation in NS2 was lethal. Therefore, to allow us to test the relevance of NS1 SUMOylation in the absence of changes in the primary sequence of NS2, we followed a previously reported methodology to separate the ORF for NS1 from that for NS2 while still allowing NS2 to be produced as a splicing product of the primary NS mRNA transcript (57). Briefly, starting with PolI-driven constructs for either wt NS1 or NS1K70AK219A, the splicing acceptor site located in NS1 was inactivated by site-directed mutagenesis.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 99%
“…Generation of rSINV expressing miR-124 has been described elsewhere (Shapiro et al 2010;Varble et al 2010). Similarly, rSINV122 was generated by cloning the mmu-miR-122 locus (chr18:65, 408,015-65,409,080) into rSINV as previously described (Shapiro et al 2010).…”
Section: Vector Design For Cytoplasmic Mirna Synthesismentioning
confidence: 99%
“…The primiR-124-2 and the TE12Q constructs have all been described elsewhere (Cheng et al 1996;Perez et al 2009;Varble et al 2010). miR-124 inserts were amplified using previously described primers flanked with BstEII linkers and were cloned directly into the SP6-based DNA plasmid.…”
Section: Virus Design Rescue and Infectionsmentioning
confidence: 99%